2015
DOI: 10.1292/jvms.14-0555
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 and AKT are vital factors in regulation of the migration of rat Schwann cells

Abstract: After peripheral nerve injury, Wallerian degeneration (WD) occurs in the distal nerve segment. During the process of degeneration, Schwann cells (SCs) dedifferentiate, proliferate and migrate to align in “bands of Büngner”, providing structural guidance and growth-promoting substrates to regenerating axons. The molecular signals that trigger SCs migration remain unclear. Here, we explored the molecular characteristics of the migration of cultured SCs prepared from rat sciatic nerves that had degenerated. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Several studies have suggested the importance of the PI3K/AKT pathway in normal Schwann cell function (Colognato & Tzvetanova, 2011;Maurel & Salzer, 2000). AKT is important for Schwann cell migration after peripheral nerve injury (Yu et al, 2015); an overexpression of AKT is sufficient to inactivate Bad and reduce apoptosis after serum withdrawal (Li, Tennekoon, Birnbaum, Marchionni, & Rutkowski, 2001). The present study shows that palmitic acid overload decreases cell viability and induces apoptosis in…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested the importance of the PI3K/AKT pathway in normal Schwann cell function (Colognato & Tzvetanova, 2011;Maurel & Salzer, 2000). AKT is important for Schwann cell migration after peripheral nerve injury (Yu et al, 2015); an overexpression of AKT is sufficient to inactivate Bad and reduce apoptosis after serum withdrawal (Li, Tennekoon, Birnbaum, Marchionni, & Rutkowski, 2001). The present study shows that palmitic acid overload decreases cell viability and induces apoptosis in…”
Section: Discussionmentioning
confidence: 99%
“…Because NMDA-Rs activated ERK1/2, Akt, and cell signaling factors that are known to function downstream of these kinases, NMDA-Rs may be clustered with other SC receptors that also regulate these 2 cell signaling factors simultaneously (3,43,(47)(48)(49). These SC receptors have been reported to regulate cell cycle progression during development, SC differentiation and myelination, SC migration, and transformations in SC phenotype that accompany the response to PNS injury.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that activation of cell signaling factors, including ERK1/2, Akt, and Rac1, promotes SC migration (3,31,43,44). We therefore studied the effects of glutamate on SC migration, as a representative metric for reporting the effects of activated cell signaling on SC physiology.…”
Section: Igrs Promote Sc Migrationmentioning
confidence: 99%
“…After peripheral nerve injury, Schwann cell migrates toward regrowing axons by regulating extracellular matrix (ECM) and ECM substrates such as fibronectin and laminin [ 34 ]. Also, extracellular signal-related kinase (ERK) 1/2 and AKT are important players for migration of Schwann cell during nerve degeneration [ 35 ]. Chang et al demonstrated that neuregulin enhanced SC migration through erbB2/3- focal adhesion kinase (FAK) pathway following nerve injury [ 36 ].…”
Section: The Migration Of Scsmentioning
confidence: 99%